Observation of the semileptonic decay B+ → pp[bar]μ+νμ - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dembiski, H.-P.; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; et al. (Journal of high energy physics, 2020)
The Cabibbo-suppressed semileptonic decay B+→pp̄μ+νμ is observed for the first time using a sample of pp collisions corresponding to an integrated luminosity of 1.0, 2.0 and 1.7 fb−1 at centre-of-mass energies of 7, 8 and 13 TeV, respectively. The differential branching fraction is measured as a function of the $$ p\overline{p} $$ invariant mass using the decay mode B+→ J/ψK+ for normalisation.
Im Titel steht der zweite Buchstabe p mit einem Oberstrich
Im Titel ist "+" jeweils hochgestellt und der zweite mu untergestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, P. d’Argent, H.-P. Dembinski, M. Dziewiecki, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, R. Kopecna, B. Leverington, H. Malygina, J. Marks, N. Meinert, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, S. Stemmle, U. Uwer, H. Viemann, R. Waldi, M. Zavertyaev, A. Zhelezov und weitere 875
Gesehen am 14.04.2021